THE LIPMAN–ZARISKI CONJECTURE IN GENUS ONE HIGHER - HANNAH BERGNER; PATRICK GRAF (Forum of Mathematics, Sigma, 2020)
We prove the Lipman–Zariski conjecture for complex surface singularities with $p_{g}-g-b\leqslant 2$. Here $p_{g}$ is the geometric genus, $g$ is the sum of the genera of exceptional curves and $b$ is the first Betti number of the dual graph. This improves on a previous result of the second author. As an application, we show that a compact complex surface with a locally free tangent sheaf is smooth as soon as it admits two generically linearly independent twisted vector fields and its canonical sheaf has at most two global sections.